The Influence of Service Quality, Brand Image and Price on Customer Satisfaction of the Taman Bukit Palem Resort Bogor Hotel - Astuti, Siti Nuranisa; Andari, Titiek Tjahja; Samsuri (MultiTech Publisher, 2024)
This research is about service quality, brand image and price on consumer satisfaction at the Taman Bukit Palem Resort Bogor Hotel. The method used is descriptive quantitative verification. Data collection through distributing questionnaires. The tests used are validity tests, reliability tests and classical assumption tests which are processed to produce multiple linear regression equations. The results of this research are that all indicators are simultaneously valid and reliable, the independent variables are proven to significantly influence the dependent variable of consumer satisfaction. Then, partially, it can be seen that the independent variables service quality (X1) and price (X3) have a positive and significant influence on consumer satisfaction (Y), while brand image (X2) does not have a positive and significant influence on the dependent variable consumer satisfaction (Y).